2021
DOI: 10.1007/s11033-021-06457-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of Interleukin-1 receptor antagonist as a treatment option in calcium pyrophosphate crystal deposition disease

Abstract: Calcium Pyrophosphate Crystal Deposition (CPPD) disease is characterized by the deposition of calcium pyrophosphate crystals in the cartilage. In most cases, it can manifest as a subclinical condition named chondrocalcinosis, often revealed by joint x-ray examination. In other cases, deposition can cause flares of arthritis, known as acute CPP crystal arthritis. In the last few years, many pathogenic pathways have been discovered. Interleukin-1 (IL-1) plays a key role in the pathogenesis of CPPD disease, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
4
0
1
Order By: Relevance
“…[ 9 ] Anakinra, which is used to treat PG, is regarded as a safe treatment in terms of side effects. [ 8 ] In our case, severe arthritis after ZA infusion was relieved after a single-day anakinra treatment, and the PG attack did not recur, with the colchicine treatment continuing in the postoperative period.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…[ 9 ] Anakinra, which is used to treat PG, is regarded as a safe treatment in terms of side effects. [ 8 ] In our case, severe arthritis after ZA infusion was relieved after a single-day anakinra treatment, and the PG attack did not recur, with the colchicine treatment continuing in the postoperative period.…”
Section: Discussionmentioning
confidence: 61%
“…[ 7 ] Interleukin-1 plays an essential role in PG, both in the inflammatory response to crystals and the pathogenesis of articular cartilage damage. [ 8 ] In case-based studies evaluating the IL-1 antagonist anakinra, it is an effective treatment in acute attack. [ 9 ] Anakinra, which is used to treat PG, is regarded as a safe treatment in terms of side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Этот факт важен, в том числе исходя из сложности подбора терапии БДПК пациентам преклонного возраста [8]. Считается, что ИЛ-1ра анакинра может быть наиболее приемлемым вариантом лечения острых артритов для пациентов, которым иная терапия противопоказана либо не дает желаемого эффекта, что в пожилом возрасте бывает довольно часто [27]. Однако характеристика артрита при БДПК в разных возрастных группах не различается [5], что согласуется с данными настоящего исследования (возраст наших пациентов, которым назначалась анакинра, варьировал от 49 до 66 лет).…”
Section: Discussionunclassified
“…Studies have demonstrated that CPP crystals induce the downregulation of the natural IL-1Ra antagonist, resulting in increased IL-1 activity. This leads to a rise in cytokines such as tumor necrosis factor-alpha (TNF-α), IL-6, and chemokines ( 38 , 39 ).…”
Section: Treatment Of Cppdmentioning
confidence: 99%